EFEKTIVITAS KOMUNIKASI AKUN INSTAGRAM @SUMBAR_RANCAK SEBAGAI MEDIA INFORMASI ONLINE PARIWISATA SUMATERA BARAT - Novi Herlina; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Instagram is one of type socia media that is not only effective for communicating, but also effective when used as a online information providers either general information or special information. One of the users who use instagram as an online special information is @sumbar_rancak Account @sumbar_rancak is an instagram account that provides special information about tourism in West Sumatra. The theory used in this research is communication effectiveness theory as the main theory and new media theory as its supporting theory. The purpose of this research is to investigate how big the effectiveness of account instagram @sumbar_rancak as a tourism information online West Sumatra.This research uses quantitative research methods, with data collection techniques that is through the spread of online questionnaires using google docs to followers @sumbar_rancak account with 400 sample counts that are determined through random sampling technique. The analysis techniques data in this research using descriptive statistical techniques.The results of this research indicate that the level of Account Instagram Effectivity @sumbar_rancak As Tourism Online Information Media West Sumatra classified as very effective. This has been proven by the result of collected data that have been measured by six indicator, each indicator reaches a scale of 3.30 on the receiver or user indicator, scale of 3.29 on the content indicator, 3.40 scale on the channel indicator ( Media), 3.30 on the format indicator, 3.22 scale on the source indicator, and 3.06 on the timing indicator. The conclusion obtained by using the average formula of all indicators is 3.26 which is included in a very effective scale range. This indicates that Instagram Account @sumbar_rancak is a very effective as a tourism online information media in West Sumatra.Keyword : Communication Effectivity, Information, Instagram, Tourism